Influence of editing pulse flip angle on J‐difference MR spectroscopy. Issue 2 (14th September 2021) - Tapper, Sofie; Hui, Steve C. N.; Saleh, Muhammad G.; Zöllner, Helge J.; Oeltzschner, Georg; Near, Jamie; Soher, Brian J.; Edden, Richard A. E.
Abstract : Purpose: To investigate the editing‐pulse flip angle (FA) dependence of editing efficiency and ultimately to maximize the edited signal of commonly edited MR spectroscopy (MRS) signals, such as gamma‐aminobutyric acid (GABA) and lactate. Methods: Density‐matrix simulations were performed for a range of spin systems to find the editing‐pulse FA for maximal editing efficiency. Simulations were confirmed by phantom experiments and in vivo measurements in 10 healthy participants using a 3T Philips scanner. Four MEGA‐PRESS in vivo measurements targeting GABA+ and lactate were performed, comparing the conventional editing‐pulse FA (FA = 180°) to the optimal one suggested by simulations (FA = 210°). Results: Simulations and phantom experiments show that edited GABA and lactate signals are maximal at FA = 210°. Compared to conventional editing (FA = 180°), in vivo signals from GABA+ and lactate signals increase on average by 8.5% and 9.3%, respectively. Conclusion: Increasing the FA of editing‐pulses in the MEGA‐PRESS experiment from 180° to 210° increases the edited signals from GABA+ and lactate by about 9% in vivo.